Evaluating Intelligence Indicators in the Sustainability of Small Cities Case Study: Nowshahr - Sadroddin Motevalli, Zohreh Nouranikootenaei, Masoumeh AmiriBesheli, Fatemeh Jafari Katrimi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Today's smart cities depend on broadband systems for every aspect of their operations. Urban systems for transportation, energy, health and education, water, sanitation, and other vital services are highly dependent on broadband networks. People in a real smart city, with better equipment to enjoy the opportunity that a smart city provides for individuals, neighborhoods and society as a whole, have the opportunity to live safer, better and more prosperous. The purpose of this study is to evaluate the indicators of intelligence in the sustainability of Nowshahr as one of the small cities in the country. Since the present study has a local-local character and is based on and using the context and context of the existing theories, principles and laws in order to answer the questions and achieve the goals, it is an applied research. Questionnaire, interview and field observation tools were used to collect information. In examining the correlation coefficient between smartening and sustainability, it has been determined that there is a direct and strong correlation between these two variables in Nowshahr.The results of the t-test of some samples show that the status of intelligent variables in Nowshahr is not in a good position with a stability approach. The results of factor analysis have shown that among the six indicators of intelligence, "smart governance" with a factor load of 0/853 has gained the highest priority from experts and specialists in smart Nowshahr with a sustainable approach. Then "smart people" with a factor load of 0/847 and "smart environment" with a factor load of 0/836 have the highest importance in terms of average factor load. In order to develop the level of intelligence and sustainability in Nowshahr, the strategy of urban smartening strategies can be developed by the city management, along with local sustainability indicators to improve the level of services to citizens. Development of intelligence level of environmental indicators (such as energy, land use, environment, and ...) can be raised too.